RADIOFREQUENCY IDENTIFICATION CURRENT AND PROSPECTIVE SCENARIO - Larrañaga, Félix (Future Studies Research Journal: Trends and Strategies, 2009)
Radio Frequency Identification Technology (RFID) that arose from World War II developments has become one of the most attractive management tools to the business environment yet has faced scarce current applicability. This study analyses the opinion of specialists engaged in the industry, trade and logistics management of diverse economic segments with views to presenting an amplified perspective of this technologies current and future behaviour, as well as its inclusion within the corporate environment. The subject matter of choice derives from the author’s personal curiosity, as leveraged by numerous publications that failed to reveal coincidental opinions and operational approaches concerning the use of this technology. This seems to have found ground given the lack of technical knowledge within both the business community and the public in general and, undoubtedly, considering its high implementation costs. The research, of bibliographical nature, concludes that effectively there are favourable and unfavourable opinions concerning this technology’s application at the surveyed industries and organizations, although most acknowledge its high potential business management efficiency and effectiveness. It is understood that only a favourable evolution of economic activities will promote the necessary investments and drive players into furthering in-depth studies concerning the varied RFID possibilities in addition to analysing the strategic convenience of its application. Key-words: RFID. Logistics. Strategic Management. Supply Chains.